Pendekatan Teori Pendidikan Anak Antara Ibnu Sina dan Jean Piaget: Pendekatan Kognitif dan Holistik - Ahmadin, Ahmadin (Mandalika Institute, 2025)
The main problem in this study is the low learning outcomes of students in the PKn subject To solve the problem of applying a Values Clarivication Technique (VCT) learning method through Public Interview Techniques. With the aim of finding out the Improvement of Student Learning Outcomes with the Values Clarivication Technik (VCT) Method Through Public Interview Techniques in Civic Education Subjects in grade VII of SMP Negeri 1 Bokan Islands, Banggai Laut Regency. The research used is Classroom Action Research, The design of this class action research refers to the Hopkins Model which is carried out in two cycles and each cycle consists of 4 stages, namely planning (planning), acting (acting), observing (observing) and reflecting (reflecting) in each cycle. This research was conducted in grade VII. Based on the results of the action test, there was an increase in student learning outcomes. Starting from the initial test to the final test of the second cycle of action. The increase can be seen from 62.76% in the first cycle and 90.11% in the second cycle. For the results of student and teacher observations, there was an increase from cycle I to cycle II. The increase can be seen from the observation of students from 41% in cycle I to 88% in cycle II, and the increase in teacher observation results can be seen from 34% in cycle I to 89.3% in cycle II. This shows that the application of the Values Clarivication Technik (VCT) Learning Method Through Public Interview Techniques on the Subject of Indonesian Foreign Policy can improve the learning outcomes of PKn students of Class VII of SMP Negeri 1 Bokan Islands, Banggai Laut Regency.